The Effects of Refilling Additional Rooting Material on Exploration Duration and Tail Damages in Rearing and Fattening Pigs - Kauselmann, Karen; Schrader, Lars; Schrade, Hansjörg; Krause, E. Tobias (Frontiers in Animal Science, 2021)
Pigs housed in commercial barns with slatted floors cannot fully perform their natural behavioral needs such as rooting or exploring. Enrichment materials can stimulate these behaviors in pigs. Here, we investigated whether exploration can be stimulated by offering additional enrichment material, i.e. chopped straw, once compared to four times daily. In two replicates each with four rearing and eight fattening pens, a total of 192 pigs with undocked tails continuously received chopped straw from a dispenser, while a stimulus to explore was given by filling the rooting area of the dispenser either once (R1) or four times (R4) daily with additional chopped straw. The dispensers were equipped with an ultra-high-frequency radio-frequency-identification (UHF-RFID) system in order to record the exploration durations of each individual pig at the dispenser. At four times throughout rearing and fattening, pigs were weighted and tail injuries and length losses were assessed. This resulted in three temporal sections within each replicate, for each of which the difference in tail length to the previous section (Δ-tail length) was calculated. Exploration durations did not change in long-term but increased from rearing throughout fattening. The refillings in which additional chopped straw was offered (R1 vs. R4) did not affect the overall exploration duration during rearing (linear mixed effects model (LME), P=0.85) or fattening (LME, P=0.66). However, descriptive evaluations showed that exploration durations decreased within the first 10-minute sequences within the hour after refilling the rooting area with additional chopped straw in both treatments (R1 and R4). Exploration durations were affected by week, day and hour within day during rearing (LME, all factors, P<0.0001) and fattening (LME, all factors, P<0.0001). Neither tail injuries nor length losses were affected by the refilling treatment (R1 vs. R4) during rearing (GLMM, both P>0.1) or fattening (GLMM, both P>0.1). Offering additional straw four times compared to once a day had no advantage in the present setting with regard to exploration duration and tail damages of pigs. However, refilling the rooting area with additional chopped straw triggered a short-term increase of exploration that decreased within one hour, thus, exploration was more spread over the day.